Strategies to Improve Environmental Comfort of Institutionalized Older Adults: A Scoping Review - Catarina Lobão; Adriana Coelho; Rocío Gil Gutiérrez; Inês Marçal; Madalena Antunes; Vítor Parola (Journal of Ageing and Longevity)
The demographic trends of an aging global population present significant challenges and opportunities for healthcare, particularly in providing optimal care environments for older adults living in long-term care facilities, with it being imperative to ensure these environments provide basic care and promote overall well-being through enhanced environmental comfort. This scoping review intends to show evidence-based practices enhancing the environmental comfort of institutionalized older people. Following the Joanna Briggs Institute’s methodology, this scoping review’s inclusion criteria included studies in English, Portuguese, or Spanish between 2013 and 2023, focused on institutionalized people over the age of 65 years residing in long-term care settings where nurses implemented strategies or interventions designed to enhance environmental comfort in which older residents themselves directly evaluated, indexed in Medline, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Scopus, Psychology and Behavioral Sciences Collection, DART-Europe, or Repositório Científico de Acesso Aberto de Portugal (RCAAP). Out of 497 initially retrieved studies, none of them met the established criteria, leading this study to be an empty review. The absence of studies meeting the inclusion criteria indicates a significant gap in the existing literature, highlighting the need for specialized training programs that equip nurses with the skills and knowledge to implement effective comfort-enhancing interventions, ensuring that the unique and challenging needs of older people are covered.